Rule Need Raises Hatred its Contemporary Applications and Images Applied Robotic Study - Al-Shehab, Abir Jassim Mohammed (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: The study aims at clarifying the meaning of the legal maxim "necessity overrides prohibition", its foundational adaptation, and highlighting its contemporary applications and legal implications. Methods: The nature of the research necessitated adherence to an inductive approach: examining the statements of jurists and legal scholars to elucidate the maxim, and employing analytical comparative methodology on legal texts and jurisprudential schools to demonstrate its legal adaptation, ancient and contemporary interpretations. Results: The maxim "necessity overrides prohibition" is explicitly mentioned in all jurisprudential schools, implicitly or explicitly, and it is a subset of the maxim "necessity permits the prohibited". It signifies that whenever there is a necessity accompanied by a legal basis, the ruling of prohibition is lifted accordingly, according to its strength. It is based on legal evidence, has foundational adaptation, regulations, and applications in various legal domains across all jurisprudential schools, and can be extrapolated in contemporary contexts. Conclusion: This maxim has its legal roots, foundational adaptation for specific circumstances, and its regulations include the existence of necessity, non-contradiction with the objectives of Islamic law, and specifying its form. It has applications in jurisprudence and contemporary contexts. The study recommended the necessity of linking jurisprudential topics with their foundations, aiding in legal representation in the domains of conflict resolution and prioritization, as well as in deriving legal rulings for occurrences.